Pengembangan Aplikasi Transaksi dan Pendataan Barang berbasis Android (Studi Kasus : Toko Gokasi) - Gilbert Osvaldo Christian; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
One of the main elements of technological development in the trading business is inventory, which requires special attention. The inventory of goods is an element of the trade sector that needs to be fulfilled. The progress and success of a business venture are influenced by the supply of goods that can meet customer needs. The problem of inventory is one of the problems that occurs in an electronic component store called the Gokasi store. The purpose of this research is to make a transaction application and collect goods data to solve problems at a shop called Gokasi. This study uses the waterfall method. In the needs analysis, there are 14 functional and 2 non-functional requirements. The design stage includes the design of activity diagrams, sequence diagrams, pseudocode, class diagrams, databases, and interfaces. The database implementation and 10 interface views are then produced during the implementation stage. The testing process produces 100% valid black-box and compatibility results. Usability testing using SUS resulted in a score of 89.16, which is included in grade B with excellent adjective ratings.